The effect of Kod Tangan Bahasa Malaysia and Bahasa lsyarat Malaysia on student achievement in Bahasa Malaysia among deaf children - Kamarudin, Diyana; Darun, Mohd Ridzuan
Previously in Malaysian curriculum, only Bahasa Melayu Kod Tangan (BMKT) is allowed in the curriculum as this is the formal language used in the Ministry of Education Malaysia. Bahasa Isyarat Malaysia (BIM) is the language developed by the Malaysian Federation of the Deaf, for the deaf people, where it is used by the deaf association in Malaysia. Bahasa Malaysia Kod Tangan or BMKT is the code used by teachers to construct sentences using formal Malay language, whereas Bahasa Isyarat Malaysia is the informal way of communication between teachers and students mainly to explain what certain words or hand signals mean (Yusoff & Mohamed, 2004). In order to fully utilize this code, teachers need to have a good understanding of the topics and subjects.